MAPPING ISLAM: New Order Policy, Mosque Distribution, and Religious Dynamics in West Java, Indonesia - Tabroni, Roni; Dachlan, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
One of the key factors shaping the religious landscape in Indonesia is the strategic policies implemented by the New Order Government. This article examines how these policies influenced the geographic distribution of mosques and the subsequent religious dynamics in West Java. Additionally, it investigates the impact of government policies on the formation and development of religious organizations and Islamic communities across different regions, with a specific focus on West Java. This study employs a historical method by analyzing government archives, historical documents, and mosque establishment data. Spatial analysis is used to correlate mosque locations with centers of social, economic, and political activity. The findings indicate that the New Order government's mosque construction policy directly shaped the spatial distribution of mosques in West Java. The placement of mosques during the New Order era prioritized areas with concentrated Muslim population, aligning with the government's strategy to monitor religious organizations. By strategically placing mosques, which often serve as the center of life for Muslim communities, the New Order aimed to control Muslim activities. This article contributes to a deeper understanding of the complex interplay between state power, religion, and spatial politics in Indonesia.